Carbon sequestration potential of silvipastoral systems in hot arid region of India: Carbon Sequestration Potential of Silvipastoral Systems in Hot Arid - Patidar, Mavji; Tanwar, S P S; Patidar , Anil; Mathur , B K; Rajora , M P (Annals of Arid Zone, 2023)
Silivipastoral systems having trees and grasses play an important role in providing fodder for sustainable livestock production in arid region, prevent soil erosion, conserve soil moisture and add organic matter to soil. A field experiment was initiated on the silvipastoral system having different trees species i.e., Hardwickia binata, Ailanthus excelsa and Colophospermum mopane in association with Cenchrus ciliaris grass at ICAR-CAZRI Jodhpur, India in the year 2003. Observations on growth, biomass production and organic soil carbon content were recorded during kharif season in the year 2015. Maximum plant height was recorded in case of H. binata whereas minimum was recorded for C. mopane. The highest canopy area was recorded in C. mopane, whereas least canopy area was recorded in case of H. binata. Highest DBH was recorded for C. mopane and least for H. binata. Specific gravity of wood of C. mopane was maximum whereas it was minimum in A. excelsa. The AGB of C. mopane (13.5 t ha-1) was maximum among the tree species whereas it was minimum in case of A. excelsa (2.6 t ha-1). Root biomass of C. mopane (3.51 t ha-1) was maximum whereas least was recorded for A. excelsa (0.67 t ha-1) which was at par with that of H. binata (0.74 t ha-1). The highest amount of carbon was sequestered by C. mopane tree (8.51 t ha-1) and least by A. excelsa (1.63 t ha-1) which was comparable with that of H. binata (1.80 t ha-1). Total Carbon sequestered by C. mopane based silvipature system. (10.19 t ha-1) was higher as compared to H. binata (3.69 t ha-1) and A. excelsa (4.45 t ha-1) based silvipasture systems. These results would help in selection of suitable silvipasture system for the arid regions of Rajasthan for sustainable land use management and increase carbon sequestration.